2006
DOI: 10.1074/jbc.m603007200
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Calpains Increase Tubular Epithelial Cell Mobility

Abstract: Calpains are intracellular Ca2؉ -dependent cysteine proteases that are released in the extracellular milieu by tubular epithelial cells following renal ischemia. Here we show that externalized calpains increase epithelial cell mobility and thus are critical for tubule repair. In vitro, exposure of human tubular epithelial cells (HK-2 cells) to -calpain limited their adhesion to extracellular matrix and increased their mobility. Calpains acted primarily by promoting the cleavage of fibronectin, thus preventing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 41 publications
6
18
0
Order By: Relevance
“…Our previous studies indicated that extracellular calpains play a role in tubular epithelium regeneration after renal ischemia/reperfusion via the detachment of FN fragments from the extracellular matrix, 31 consistent with findings of other groups. 32 Thus, to identify molecular mechanisms whereby extracellular calpains speed up endothelium regeneration, we evaluated the ability of calpains to hydrolyze proteins of extracellular matrix in 1D SDS-PAGE experiments (Supplemental Figure VII).…”
Section: Proangiogenic Function Of Extracellular Calpains Involves Fisupporting
confidence: 92%
See 1 more Smart Citation
“…Our previous studies indicated that extracellular calpains play a role in tubular epithelium regeneration after renal ischemia/reperfusion via the detachment of FN fragments from the extracellular matrix, 31 consistent with findings of other groups. 32 Thus, to identify molecular mechanisms whereby extracellular calpains speed up endothelium regeneration, we evaluated the ability of calpains to hydrolyze proteins of extracellular matrix in 1D SDS-PAGE experiments (Supplemental Figure VII).…”
Section: Proangiogenic Function Of Extracellular Calpains Involves Fisupporting
confidence: 92%
“…Previous studies have suggested a role for protease-induced cleavage products of extracellular matrix proteins in vascular development and repair. 36 Because calpains are known to cleave FN, 31,32 we focused our studies on this protein. Exposure of native human FN to calpains generated various fragments encompassing the C-terminal heparin-II domains 9 to 10 and 13 to 14 which bind the ␣ 5 ␤ 1 integrin and VEGF, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its effects on cell-cell contacts, EGFR activity can affect cell-matrix contacts by induction of calpain activity and cleavage of fibronectin and/or focal adhesion component talin [32][33][34]. In our setting, the modest CSE-induced increase in high-frequency capacitance reflected effects on cell-matrix contacts, and the presence of AG1478 abrogated these effects.…”
Section: Discussionmentioning
confidence: 72%
“…For instance, externalized calpains activate anti-inflammatory cytokines (TGF-b) (13) and inactivate proinflammatory proteins (chemerins) (14). In addition, we demonstrated that extracellular calpains participate in both epithelium regeneration in a model of acute kidney injury (15) and angiogenesis in models of kidney inflammation (10). The opposite activities of intra-and extracellular calpains raise questions regarding the mechanisms of calpain secretion.…”
mentioning
confidence: 91%